2007
DOI: 10.3354/dao074209
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR for quantification of viable Renibacterium salmoninarum in chum salmon Oncorhynchus keta

Abstract: Quantification of msa gene mRNA of Renibacterium salmoninarum, the causative agent of bacterial kidney disease (BKD), was investigated using reverse transcription followed by real-time PCR assay on R. salmoninarum in culture, and in experimentally challenged chum salmon Oncorhynchus keta fry kidney tissues (total of 70 samples) after intraperitoneal (i.p.) injection and bath infection. Correlations of msa gene mRNA concentrations with culturable cell concentrations (as colony forming units [CFU]), determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…Detection of bacterial DNA or protein is not necessarily indicative of viable cells, which can be confirmed by growth in culture. Analysis for bacterial RNA, which is extremely labile and produced only by living cells, has been proposed as a marker for viable Renibacterium salmoninarum (Cook & Lynch 1999, Suzuki & Sakai 2007 Suzuki & Sakai (2007) observed elevated DNA concentrations but minimal or no mRNA or culture growth during the early course of a disease challenge (see also our Fig. 5B), indicating that the DNA signal can dominate during expanding infections.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Detection of bacterial DNA or protein is not necessarily indicative of viable cells, which can be confirmed by growth in culture. Analysis for bacterial RNA, which is extremely labile and produced only by living cells, has been proposed as a marker for viable Renibacterium salmoninarum (Cook & Lynch 1999, Suzuki & Sakai 2007 Suzuki & Sakai (2007) observed elevated DNA concentrations but minimal or no mRNA or culture growth during the early course of a disease challenge (see also our Fig. 5B), indicating that the DNA signal can dominate during expanding infections.…”
Section: Discussionmentioning
confidence: 93%
“…Teska et al 1995, Griffiths et al 1996, Miriam et al 1997, Suzuki & Sakai 2007. In the context of previous studies using multiple assays, a conceptual model for interpreting our ELISA and qPCR results may be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Since these assays measure RNA rather than DNA, RT-qPCR may be better able to discriminate live from dead bacteria. One caveat is that differential regulation of R. salmoninarum genes may occur during the infection cycle; however, a previous study in coho salmon (Oncorhynchus kisutch) found good correlation between msa mRNA and genomic DNA copy number in infected samples (Suzuki & Sakai 2007). Our RT-qPCR methodology has been previously described in detail (Purcell et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…and viruses (Bode et al 2004, Kocagoz et al 2005, Takahashi et al 2007, Tomaso et al 2007, Abril et al 2008, Kidd et al 2008. In recent years, fish disease diagnosticians have used this technique to identify and quantify bacterial, viral, and parasitic fish pathogens such as Aeromonas salmonicida, Flavobacterium columnare, Renibacterium salmoninarum, Henneguya ictaluri, largemouth bass virus, and recently Francisella piscicida in Norwegian cod (Balcázar et al 2007, Getchell et al 2007, Panangala et al 2007, Suzuki & Sakai 2007, Griffin et al 2008, Ottem et al 2008. The high sensitivity, high specificity, and short turnaround time for results make this technique an attractive replacement method for conventional diagnostic techniques (Espy et al 2006).…”
Section: Introductionmentioning
confidence: 99%